Pengaruh Good Corporate Governance Dan Profitabilitas Terhadap Harga Saham Pada Perusahaan Corporate Governance Perception Index - Nurul Huda; Irwansyah Irwansyah; Dhina Mustika Sari (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2020)
Nurul Huda. 2019. Effects of Good Corporate Governance (GCG) and Profitability on Stock Prices (Empirical Study of Companies Participating in Corporate Governance Perception Index) Under the guidance of Mr. Irwansyah and Mrs. Dhina Mustika Sari. This research was conducted at a participant company Corporate Governance Perception Index which was listed on the Indonesia Stock Exchange (IDX). The purpose of this study is to test and analyze whether good corporate governance and profitability affect stock prices. The type of data used is secondary data derived from CGPI reports obtained from IICG, as well as financial reports listed on the IDX for the period 2012-2016. This study uses a multiple linear regression method with SPSS version 20. These results indicate that the variable Good Corporate Governance has a positive and not significant effect on stock prices, while the profitability variable has a positive and significant effect on stock prices.